Patterns of red tree vole distribution and habitat suitability: implications for surveys and conservation planning. Issue 12 (28th December 2016) - Rosenberg, Daniel K.; Davis, Raymond J.; Van Norman, Kelli J.; Dunk, Jeffrey R.; Forsman, Eric D.; Huff, Robert D.
Abstract: Environmental regulations often require wildlife surveys prior to habitat disturbance to avoid impacts or as the basis for planning mitigation, yet project‐level surveys may not provide the insights needed to guide long‐term management. Management of the red tree vole ( Arborimus longicaudus ) has largely been based on such surveys. As an alternative approach, we evaluated distribution patterns using frequency of red tree vole occurrence and habitat suitability models to guide conservation planning. We developed a suite of models based on subsets of covariates from two previously developed models and evaluated the extent to which spatial covariates improved the models. We used presence–absence data that were collected from 364 randomly selected 1‐ha Current Vegetation Survey and Forest Inventory and Analysis plots to develop models and describe occurrence patterns. The best models included a spatial covariate, maximum tree diameter, distance from suitable habitat, forest age class, and the interaction between maximum tree diameter and forest age class. We compared performance of the previously published models, our best model, and an ensemble model that used predictions from all three models. Under the ensemble model, correct classification rates were relatively high and considerably improved, suggesting that the application of all three models provided greater accuracy than any individual model. We argue that habitat models, coupled with spatial patterns of the frequency of occurrence, can provide useful tools for addressing species management and may provide more insight than project‐level surveys. The use of habitat suitability models can therefore be closely tied to red tree vole management decisions and conservation strategies, as well as reducing survey costs that otherwise often make projects infeasible.